Strategic management - Thompson, John L. 1931- (Thomson, 2001)
This edition, which now includes fully classroom-tested case studies, covers the core aspects of the business strategy syllabus as well as reflecting the cutting edge of strategic management thought.
Keywords: Strategisch management; Industrial management; Strategic planning; Entscheidungsfindung; Strategisches Management; Lehrbuch